2019
DOI: 10.1074/jbc.ra118.006325
|View full text |Cite
|
Sign up to set email alerts
|

Covalent modification of Cys-239 in β-tubulin by small molecules as a strategy to promote tubulin heterodimer degradation

Abstract: Clinical microtubule-targeting drugs are functionally divided into microtubule-destabilizing and microtubule-stabilizing agents. Drugs from both classes achieve microtubule inhibition by binding different sites on tubulin and inhibiting or promoting polymerization with no concomitant effects on the protein levels of tubulin heterodimers. Here, we have identified a series of small molecules with diverse structures potentially representing a third class of novel tubulin inhibitors that promote degradation by cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 34 publications
1
53
0
Order By: Relevance
“…However, the tubulin inhibitors identified to date have no effects on tubulin protein levels. Previous experiments by our group showed that small molecules covalently bound to the Cys239 site, including T0070906, T007-1, and T138067, promoting tubulin degradation (Yang et al, 2019). These small molecules were collectively classified as the third type of tubulin inhibitor-tubulin degradation agent.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the tubulin inhibitors identified to date have no effects on tubulin protein levels. Previous experiments by our group showed that small molecules covalently bound to the Cys239 site, including T0070906, T007-1, and T138067, promoting tubulin degradation (Yang et al, 2019). These small molecules were collectively classified as the third type of tubulin inhibitor-tubulin degradation agent.…”
Section: Discussionmentioning
confidence: 96%
“…Our data showed that WIT forms covalent bonds with Cys303 and Cys239 of b-tubulin. Moreover, the bond between WIT and Cys239, but not Cys303, was responsible for tubulin degradation, providing another example of a small molecule that acts as a covalent modifier of Cys239 in b-tubulin to promote tubulin degradation (Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…That some of the active compound-cysteine interactions led to protein degradation without requiring a separate E3 ligase-directing ligand (e.g., EV-3-mediated degradation of BIRC2/3) underscores the potential for covalent modification by small molecules to directly affect protein stability in cells (Foulkes et al, 2018;Jones, 2018;Schreiber, 2019;Yang et al, 2019). We do not yet understand how EV-3 promotes BIRC2 and BIRC3 degradation, but this could involve disruption of protein-protein interactions proximal to the compound-modified cysteines in these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…We have done three biological repeats. Then the following label-free quantitative proteomic analysis of these samples were carried out following the procedure as described previously [13].…”
Section: Label Free Quantitative Proteomicsmentioning
confidence: 99%